Les nouveaux pays industrialisés : Stratégies de développement industriel – le cas de la Corée du Sud et du Brésil - Albert, Alain; Crener, Maxime (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
In the introductory remarks of this article the authors examine the birth of the newly industrialized countries and the emergence of a new international division of labor. After stressing the two modes of the industrial strategy followed by these countries, the authors look at two newly industrialized countries (Brazil and South Korea). These specific countries due to the interplay of both, objective factors (natural resources, location, manpower...) and policy choices have followed divergent development strategies. The authors conclude that it is not so much the classical policy dilemma import substitution vs expert promotion that will determine the future of these semi-industrialized countries, than their ability to master the technological know-how that sustains their industrial development. The new technological trends in robotics and telematics constitute powerful factors of relocation which may threaten the long run growth prospects of the semi-industrialized countries.